Penggembalaan Kepada Remaja yang Kurang Percaya Diri di Jemaat GMIM Maesa Rumoong Bawah - Lempas, Alessandro (Educatio Christi, 2022)
This article discusses how to shepherd teenagers who lack self-confidence in the GMIM Maesa Rumoong Bawah congregation. Mentoring teenagers who lack self-confidence is an approach that aims to help teenagers overcome feelings of lack of self-confidence and build positive self-confidence. Pastoral care carried out on teenagers can increase self-esteem, social skills and the ability to face challenges in everyday life. This mentoring also helps teenagers feel supported, accepted, and more motivated to reach their potential. Teenagers as the young generation of the Church should be the Salt and Light of the world among Teenagers.